The Effect of Current Ratio, Debt to Equity Ratio, Debt to Asset Ratio, and Total Asset Turnover on The Financial Performance of Property and Real Estate Companies Listed in The Idx For The 20162020 Period - Silviana Rachman; Subur Karyatun; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to determine whether the Current Ratio (CR), Debt to Equity Ratio (DER), Debt to Asset Ratio (DAR), and Total Asset Turnover (TATO) on Financial Performance. This study was processed using the eviews 10 application. In this study, there were 79 population of Property and Real Estate companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The sample of this research used purposive sampling method. Based on the criteria that have been set, then obtained 20 samples of companies that will be studied in this study. The results of this study show that partially, the Current Ratio (CR) has a positive and insignificant effect on the financial performance of property and real estate companies listed on the IDX in 2016-2020. The Debt to Equity Ratio (DER) has a negative and insignificant effect on the financial performance of property and real estate companies listed on the IDX in 2016-2020. Debt to Asset Ratio (DAR) has a negative and insignificant effect on the financial performance of property and real estate companies listed on the IDX in 2016-2020. Total Asset Turnover (TATO) has a positive and significant impact on the financial performance of property and real estate companies listed on the IDX in 2016-2020.